A ATUALIDADE DO PENSAMENTO FREIREANO: UMA PONTE DIALÓGICA COM A LINGUÍSTICA APLICADA - Lima, Ana Maria Oliveira (2021)
The article focuses on Freirean ideas, while comparing the notions of language and identity, themes that are referenced in Freirean work and in Applied Linguistics. It deals with sociological, educational, and language-related aspects, which show us paths for a dialogical approach with Critical Applied Linguistics through a transdisciplinary perspective. The transdisciplinarity is mobilized, in this study, by the connection between the areas of knowledge that have specific objects but that reveal the need to compose a network to interpret the ethical conduct of research. Thusly, we contributed to the discussion about the actuality of the Freirean thought, in a constant search for its acceptance in and for the world. The methodological pathway is bibliographic in nature, presenting the Freirean pedagogy articulated with Applied Linguistics from the perspective of language, dialogue and identities - concerns which arose during the Master's research. We conclude that, in contemporary times, the Freirean pedagogy, collated with Applied Linguistics, is updated in the reaffirmation of the act of educating as an ethical act and, consequently, in the emancipation of the human being, as postulated by Freire and by Applied Linguistics.